Sosialisasi Penggunaan Strategi Inkuiri mengembangkan Kinestetik Di SMA Negeri 1 Angkola Barat Tahun Pelajaran 2023-2024 - Elnila Caniago; Siti Maryam Pane; Rizki Fadila; Fita Delia Gultom; Candra Irawan; Nova Christina Dewi (Jurnal Transformasi Pendidikan Indonesia, 2023)
The curriculum is a learning program that aims to advance education in schools. Much has been done to advance the world of education, especially in curriculum development which has undergone changes from time to time. This is done to advance students to become better students in achieving learning with more optimal results in accordance with mutual expectations. Students are given the freedom to choose a learning style that suits their interests and talents, which is one of the characteristics of an independent curriculum. Students have different learning styles consisting of visual, audiotorial and kinesthetic learning styles, which are types of learning styles that make students have different learning interests. Learning also requires an interesting strategy in developing student learning, with an interesting strategy students can become more enthusiastic and more interested in learning. This is the basis for teachers to develop themselves into creative, innovative teachers who can make students into material that must be advanced in the world of education.The training carried out at SMA Negeri 1 Angkola Barat is expected to provide solutions for teachers in overcoming learning problems and provide input in developing more creative and innovative teachers.